THE USE OF POP UP BOOK MEDIA IN WRITING DESCRIPTIVE TEXT AT VII GRADE IN SMP NEGERI 1 LAWE ALAS ACADEMIC YEAR 2022/2023 - Ayu Anggraini Putri. S; James Marudut; Abdul Halim (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This research deals with the use of pop up book media to improve students’ descriptive text writing class VII SMP Negeri 1 Lawe Alas Academic Year 2022/2023. Its objective is to find out whether the use of pop up book media has a significance effect in writing descriptive text. Population used in this research of class VII were 38 and all samples used in this research were 38 students. The method used in this research is an experimental method with a one group as pre-test and post-test design .This research was carried on using quantitave method. The data was analysed by using t-test. The researcher found the pre-test mean = 56,18 , deviation standard = 5,86 and experienced an increase in the pos-ttest mean = 79,34 deviation standard = 4,10. From this analysis, writer found that guided pop up book media has significance in teaching writing descriptive text. It can be proved by the result of the analysis showed that “ ” observed about 26,02 was higher than “t-table” about 2,026 with the level significance is 5% it implies that the teacher of English should use pop up book media in teaching writing descriptive text so that the teaching and learning process can be successful.